Fusobacterium nucleatum infection-induced neurodegeneration and abnormal gut microbiota composition in Alzheimer’s disease-like rats - Yan, Caixia; Diao, Qilin; Zhao, Yuxi; Zhang, Cheng; He, Xiaoya; Huang, Ruijie; Li, Yan (Frontiers in Neuroscience, 2022)
Objective To explore whether F .nucleatum could lead to behavioral and pathological changes in Alzheimer's disease(AD) model rat and whether they could affect the gut microbiota. Methods The cognitive ability and alveolar bone loss of SD rats were tested by Morris water maze and Micro-CT respectively; HE staining and immunohistochemistry were used to analyze the pathological changes and Aβ protein in brains; The expression of p-Tau 181 in brain was detected by WB; Use PCR and limulus amebocyte lysate assay to detect the virulence genes of F. nucleatum in brain and serum LPS; The gut microbiota was analyzed by 16S rRNA gene sequence. Results We successfully constructed periodontitis with AD-like rat model, and oral infection with F .nucleatum could induce increased alveolar bone loss and learning impairment. Additionally, F. nucleatum exposure increased the Aβ1-42 expression by about 1/4 (p<0.05), p-Tau181 by about 1/3 (p<0.05) and serum LPS (p<0.05) in AD rats. Moreover, F. nucleatum could change the gut microflora composition in AD rats, accompanied by a significant increase in the abundance of Streptococcus and Prevotella. Conclusion Oral infection with F .nucleatum could contribute to abnormalities in Cognitive ability and pathological change of brain in AD-like rat, which may be related to abnormal gut microbiota composition.